Does it matter who makes the financial decisions? An exploratory study of married couples’ financial decision-making and relationship satisfaction - Archuleta, Kristy L.; Grable, John E. (My University, 2013)
How couples make financial decisions is known to be associated with relationships satisfaction. The current study uses symbolic interaction theory to examine how one’s involvement in financial decision-making and their satisfaction is related to relationship satisfaction. The results from this study indicate that whether couples make decisions jointly or not is nearly as important as the level of satisfaction they have with their involvement in financial decision-making process. The findings suggest implications for educators, financial therapists, and other professionals working with couples and their financial issues, as well as opportunities for further research in this area.
Keywords: Financial decision-making involvement; Role satisfaction; Financial decision-making role satisfaction; Relationship satisfaction